Implementasi Bimbingan Mengaji dengan Metode Yanbu’a sebagai Upaya Pembentukan Karakter Religiusitas pada Anak TPQ As-Sidiq Desa Talang Sebaris - Adrian Topano; Indah Oktaviani; Novita Kemala Dewi; Shella Pironica; Deva Surya Firdaus; Robi Riyansyah; Lidya Damayanti (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Religious education and character education are two related concepts. In its application, Al-Quran teaching plays a very important role in shaping children's character through guidance, continuous education and advice to instill religious, independent and communicative qualities in them from an early age. The aim of this research is to develop the implementation of religious character in higher education religious activities. The research methodology used is qualitative. With religious education that teaches the art of reading the Koran and its translations, the role of Taman Al-Coran (TPQ) is very important in forming the character of babies from an early age. Apart from that, there are other religious practices, such as memorizing short poetry and daily prayers, which can indirectly provide Islamic life lessons. However, a child's character must also be shaped and guided by his family so that he grows into a good person. The application of religious character in religious activities takes the form of participation in what are called "testimony and prayer activities" (Dhuha), direct direction of tahfidz, tilawati, and Friday blessing activities carried out in the context of santri activities. develop religious character. There is a positive correlation, meaning that there is a positive influence of religious activities on students' religious character. Religious activities are a useful means of developing and practicing religious character. Character development through positive habits will give birth to the habit of appreciating lessons, values, thoughts, ideology, or even doctrine, so that it becomes a belief and fosters a sense of self-awareness of reality or normative values ​​that appear in actions and attitudes. With the aim of being applicable to all schools in Indonesia, this research has implications for the growth of religious character in education.